2012
DOI: 10.1074/jbc.m112.370205
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Starch Breakdown, Acetate Assimilation, and Photosynthetic Cyclic Electron Flow in Chlamydomonas reinhardtii

Abstract: Background: Most green microalgae grow photoautotrophically and heterotrophically. Results: The origin of chloroplast reductants in the dark is starch and/or acetate. Conclusion: It is possible to distinguish between these two carbon reserves and measure the reducing flux of carbohydrate catabolism using spectroscopic methods. Significance: The glycolytic flux in the chloroplast of green algae is faster than in plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
88
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(96 citation statements)
references
References 44 publications
5
88
0
2
Order By: Relevance
“…The absorbance changes at 705 nm under PSII-inhibited conditions are proportional to the oxidation/reduction of PSI (Alric, 2010;Johnson and Alric, 2012). These P700 absorbance changes shown in Figure 5 are attributed to redox turnover at PSI due to CEF (Fig.…”
Section: Total Psi Turnover Rate Falls During N Deprivationmentioning
confidence: 99%
“…The absorbance changes at 705 nm under PSII-inhibited conditions are proportional to the oxidation/reduction of PSI (Alric, 2010;Johnson and Alric, 2012). These P700 absorbance changes shown in Figure 5 are attributed to redox turnover at PSI due to CEF (Fig.…”
Section: Total Psi Turnover Rate Falls During N Deprivationmentioning
confidence: 99%
“…Chlamydomonas cells can grow phototrophically and can also metabolize acetate and related compounds to grow mixotrophically or heterotrophically. The relationship between these modes of growth is complex and involves partial suppression of photosynthesis and alterations in gene expression when acetate is present (Heifetz et al, 2000;Boyle and Morgan, 2009;Johnson and Alric, 2012;Roach et al, 2013;Chapman et al, 2015). However, very little is known about intracellular signaling pathways that sense carbon source and control carbon metabolism and utilization in Chlamydomonas.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, as already pointed out in Refs. 29, 67, the observation that after a few minutes of illumination CEF reaches a steady state value implies that the "leak" of reducing power resulting from the CO 2 -reducing pathway, the implication of which has been discussed above, is compensated for by a constant influx of reducing power, which likely stems from starch and glucose catabolism (68). Now that we have demonstrated that the reoxidation of the pool of electron acceptors is sufficient to alleviate the unproductive buildup of charge-recombining PSI, we may reason that, similarly, the spontaneous consumption of reducing power is responsible for the alleviation of the acceptor side limitation after a prolonged incubation of anoxia in the dark.…”
mentioning
confidence: 99%